Analysis of the Motor Activities of Professional Polish Soccer Players - Andrzejewski Marcin (Polish Journal of Sport and Tourism, 2016)
Introduction. The aims of the present study were to determine the activity profiles of a large sample of Polish Premier League soccer players during elite-standard soccer matches depending on their position on the pitch and the intensity range of physical activity. Material and methods. The study sample comprised 1,178 players in 5 outfield positions: external defenders (ED, n = 289), central defenders (CD, n = 307), central midfield players (CM, n = 327), external midfield players (EM, n = 152), and forwards (F, n = 103). Altogether, 81 Polish League games held during four domestic seasons (2010-2011, 2011-2012, 2012-2013, and 2013-2014) were used in the analysis. A semi-automatic computerised player tracking system (Amisco Pro®, version 1.0.2, Nice, France) was applied to create the match activity profiles of the teams. Results. The results of statistical analysis revealed that the average total distance covered by all the players (n = 1,178) was 11,313 ± 852 m. With respect to the players’ position on the pitch, the central midfielders travelled the longest average distance (11,894 ± 765 m) during the game. The longest distance was covered in the V1 intensity range (62%), followed by V2 (15%), V3 (10%), V4 (8%), V5 (3%), and V6 (2%). Conclusions. The objective of this study was to verify the differences among playing positions and to quantify the demands placed on elite Polish soccer players in each individual position during match play. While analysing elite-level match play in terms of the overall distance covered in different categories of intensity, we found a number of statistically significant differences between different playing positions. The data presented in this study can be regarded as norms for elite soccer players, serve for present and future comparison, and represent the scientific basis for developing position-specific conditioning/training protocols in soccer.